Identification of DNA methylation based prognostic subtype and signature in epithelial ovarian cancer - Jingjing Zhou; Yuxin Chen; Wei Liu; Chao Wang; Lei Liu; Wei Geng; Linqing Chai; Dong Yang; Hongji Dai; Haixin Li; Yanrui Zhao; Kexin Chen; et al. (Human Genetics, 2026)

Characteristics of microplastics in soil and throughfall and their relationships with meteorological factors in a temperate forest ecosystem of the Changbai Mountains - Lei Xie; Yingtong Zhou; Guanhua Dai; Xingbo Zheng; Xinchang Kou; Wei Guo; Jiaxin Liu; Junni Wang; Mingkai Leng; Shihan Xu; Xiaoyue Liu; Zejun Tong; et al. (Journal of Hazardous Materials, 2026)

Inference of pile capacity from distributed strain sensing via PDE-constrained optimization - Yaobin Yang; Gyu-Beom Shin; Loizos Pelecanos; Chien-Chih Wang; Linqing Luo; Kenichi Soga (Computers and Geotechnics, 2026)

Antioxidant capacity is a key factor in the difference in thermal tolerance between massive Porites lutea and branching Acropora formosa - Linqing Meng; Ronghua Tan; Zunyong Xiao; Jinlian Chen; Zhihua Huang; Yonggang Wang; Enguang Yang; Yupeng Zhou; Mingpei Xu; Kefu Yu; Wen Huang (Marine Pollution Bulletin, 2025)

Constructing high-performance solid-state electrolyte interface and anchoring residual solvents for long-cycle lithium-metal batteries - Shi Zhou; Min Liu; Bangfu Yin; Xiaoyi Chen; Lingguang Yi; Linqing Wang; Jiali Liu; Huahui Zhao; Jun Li; Li Yang; Hong Liu; Xianyou Wang (Chemical Engineering Journal, 2025)

Failure Characteristics of Rock Mass Under the Coupled Action of Three-Way Isotropic Confining Pressure and Blast Loading - Yanbing Wang; Zhehang Huang; Yangyang Li; Renshu Yang; Linqing Li (Rock Mechanics and Rock Engineering, 2025)

Current Forest Carbon Offset Buffer Pool Contributions Do Not Adequately Insure Against Disturbance‐Driven Carbon Losses - William R. L. Anderegg; Anna T. Trugman; German Vargas G.; Chao Wu; Linqing Yang (Global Change Biology, 2025)
Nature‐based climate solutions in Earth's forests could strengthen the land carbon sink and contribute to climate mitigation, but must adequately account for climate risks to the durability of carbon storage. Forest carbon offset protocols use a “buffer pool” to insure against disturbance risks that may compromise durability. However, the extent to which current buffer pool tools and allocations align with current scientific data or models is not well understood. Here, we use a tropical forest stand biomass model and an extensive set of long‐term tropical forest plots to test whether current buffer pool contributions are adequate to insure against observed disturbance regimes. We find that forest age and disturbance regime both influence necessary buffer pool sizes. In the majority of disturbance scenarios in a major carbon registry buffer pool tool, current buffer pools are substantially smaller than required by carbon cycle science. Buffer pool tools and estimates urgently need to be updated to accurately assess disturbance regimes and climate change impact on disturbances based on rigorous, open scientific datasets for nature‐based climate solutions to succeed.

Experimental research on thermal transient flow characteristics of control rod hydraulic drive system - Benke Qin; Linqing Yang; Yun Li; Yanlin Li; Hanliang Bo (Annals of Nuclear Energy, 2025)

Application of edible insects to food products: A review on the functionality, bioactivity and digestibility of insect proteins under high-pressure/ultrasound processing - Jing Yang; Yan Chen; Linqing Zhang; Shuling Zhou; Linfeng You; Jiajia Song (Food Chemistry, 2025)

High- and low-temperature stress responses of Porites lutea from the relatively high-latitude region of the South China Sea - Wen Huang; Zhihua Huang; Enguang Yang; Linqing Meng; Jinlian Chen; Ronghua Tan; Zunyong Xiao; Yupeng Zhou; Mingpei Xu; Kefu Yu (Marine Environmental Research, 2025)

Heat-tolerant subtropical Porites lutea may be better adapted to future climate change than tropical one in the South China Sea - Wen Huang; Jinlian Chen; Enguang Yang; Linqing Meng; Yi Feng; Yinmin Chen; Zhihua Huang; Ronghua Tan; Zunyong Xiao; Yupeng Zhou; Mingpei Xu; Kefu Yu (Science of The Total Environment, 2025)

Phytotoxic effects of Perfluorooctane sulfonate on the physiological responses of the seaweed Gracilaria lemaneiformis - Zhiwei Liu; Linqing Liu; Yufeng Yang; Weiqiu Liu; Xian Sun (Algal Research, 2024)

Analysis of the influence of interlayer discontinuity conditions on the dynamic responses of multilayered poroelastic soil - Han Zejun; Zhang Junfeng; Yang Linqing; Hou Zhenkun; Yuan Bingxiang (Computers and Geotechnics, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Heat‐tolerant intertidal rock pool coral Porites lutea can potentially adapt to future warming - Wen Huang; Linqing Meng; Zunyong Xiao; Ronghua Tan; Enguang Yang; Yonggang Wang; Xueyong Huang; Kefu Yu (Molecular Ecology, 2024)
The growing threat of global warming on coral reefs underscores the urgency of identifying heat‐tolerant corals and discovering their adaptation mechanisms to high temperatures. Corals growing in intertidal rock pools that vary markedly in daily temperature may have improved heat tolerance. In this study, heat stress experiments were performed on scleractinian coral Porites lutea from subtidal habitat and intertidal rock pool of Weizhou Island in the northern South China Sea. Thermotolerance differences in corals from the two habitats and their mechanisms were explored through phenotype, physiological indicators, ITS2, 16S rRNA, and RNA sequencing. At the extremely high temperature of 34°C, rock pool P. lutea had a stronger heat tolerance than those in the subtidal habitat. The strong antioxidant capacity of the coral host and its microbial partners was important in the resistance of rock pool corals to high temperatures. The host of rock pool corals at 34°C had stronger immune and apoptotic regulation, downregulated host metabolism and disease‐infection‐related pathways compared to the subtidal habitat. P. lutea , in this habitat, upregulated Cladocopium C15 (Symbiodiniaceae) photosynthetic efficiency and photoprotection, and significantly increased bacterial diversity and coral probiotics, including ABY1, Ruegeria , and Alteromonas . These findings indicate that rock pool corals can tolerate high temperatures through the integrated response of coral holobionts. These corals may be ‘touchstones’ for future warming. Our research provides new insights into the complex mechanisms by which corals resist global warming and the theoretical basis for coral reef ecosystem restoration and selection of stress‐resistant coral populations.

“Fluorescence-wavelength” label-free POCT tandem with “fluorescence-photothermal” nanobody-immunosensor for detecting BSA and β-lactoglobulin - Shijie Li; Linqing Nie; Lu Yang; Dancai Fan; Junping Wang; Yaozhong Hu; Yan Zhang; Shuo Wang (Food Chemistry, 2024)

The chromatin remodeling protein BPTF mediates cell cycle, proliferation and apoptosis in porcine ovarian granulosa cells - Dayu Wang; Xinyue Lu; Yuan Jiang; Linqing Pan; Fuquan Zhu; Aochen Yu; Mingyue Zhao; Meng Yang; Jiaying Bi; Xu He; Honglin Liu; Juan Li (Theriogenology, 2023)

Research hotspots and trends in discovery of anticancer agents from algae: A 20-year bibliometric and visualized analysis based on Web of Science and CiteSpace - Kun Gao; Meng Zhang; Linqing Li; Mengting Yang; Qilin Zheng; Qiaoqiao Liu; Ruoxu Ning; Zheng Gao; Xiangyuan Deng (Algal Research, 2023)

Feasibility of growing microalgae on wastewaters collected from a vinegar plant for, concurrently, nutrient removal and biomass production - Zheng Gao; Kun Gao; Linqing Li; Mengting Yang; Pengfei Cheng; Qilin Zheng; Meng Zhang; Ruoxu Ning; Qiaoqiao Liu; Roger Ruan; Xiangyuan Deng (Algal Research, 2023)

Transient flow characteristics analysis on the step-up process of control rod hydraulic drive system - Linqing Yang; Benke Qin; Hanliang Bo (Annals of Nuclear Energy, 2023)

Lower cold tolerance of tropical Porites lutea is possibly detrimental to its migration to relatively high latitude refuges in the South China Sea - Wen Huang; Enguang Yang; Kefu Yu; Linqing Meng; Yonggang Wang; Jiayuan Liang; Xueyong Huang; Guanghua Wang (Molecular Ecology, 2022)
As high temperature stress due to climate change threatens tropical corals, cooler areas at relatively high latitudes may be potential refuges. Tolerance to low temperatures is critical in determining whether corals can successfully migrate to higher latitudes. However, the physiological and molecular adaptations that protect corals from low temperature stress are unclear. In this study, scleractinian Porites lutea samples from the tropical Xisha Islands (XS) and subtropical Daya Bay (DY) in the South China Sea were subjected to a reduction in ambient temperature from 26 to 12°C. Differences in physiological changes and gene expression were analysed. P. lutea from both XS and DY exhibited physiological bleaching under low temperature stress, and the Symbiodiniaceae density, Fv/Fm, and chlorophyll‐α content were significantly reduced. Symbiosome antioxidative stress and metabolic enzyme activity first increased and then decreased. RNA‐seq analysis showed that the host responded to low temperature stress by activating immune, apoptotic, and autophagic pathways and reducing metabolic levels. Nevertheless, Symbiodiniaceae lacked the physiological regulatory capacity to adapt to low temperatures. The lower cold tolerance of XS tropical P. lutea may attribute to lower oxidative stress resistance, lower photosynthetic capacity, worse energy supply, and higher susceptibility to bacterial and viral infections and diseases in XS corals. The difference in cold tolerance may result from genetic differences between the geographic populations and is possibly detrimental to the migration of tropical coral to relatively high latitude refuges. This study provides a theoretical basis for anthropogenically assisted coral migration as a response to global change.

Lactobacillus reuteri KT260178 Supplementation Reduced Morbidity of Piglets Through Its Targeted Colonization, Improvement of Cecal Microbiota Profile, and Immune Functions - Jiajun Yang; Chonglong Wang; Linqing Liu; Minhong Zhang (Probiotics and Antimicrobial Proteins, 2020)

The role of reactive oxygen species in silicon dioxide nanoparticle-induced cytotoxicity and DNA damage in HaCaT cells - Chunmei Gong; Gonghua Tao; Linqing Yang; Jianjun Liu; Haowei He; Zhixiong Zhuang (Molecular Biology Reports, 2012)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)